Unraveling green information technology systems as a global greenhouse gas emission game-changer - Katundu Imasiku; Valerie Thomas; Etienne Ntagwirumugara (Administrative Sciences, 2019)
Green information technology systems (Green ITS) are proposed as a strategy to reduce greenhouse gases (GHGs) emissions and other environmental impacts while supporting ecological sustainable development. The Green ITS concept combines both Green information technology (IT) and Green information system (IS) applications. The Green ITS concept has the potential to combat the carbon emission problem globally, beyond simply Green IT, because it combines management, organizational, and technology dimensions of climate change mitigation and adaptation, especially if supported by global policy. Examples include life cycle assessment software for measuring GHG emissions, and software for monitoring GHG emissions. Previous studies on environmental burdens such as GHGs, water and air pollution, energy losses and other forms of waste alongside socio-economic dependent variables including renewable resources and climate change policies are reviewed and synthesized. The research analysis conjointly points to the usage of renewable resources such as solar and wind as a critical strategy to scale back GHG emissions and enhance green growth. Empirical evidence shows that developed countries can reduce their carbon emissions while developing countries can utilize carbon emission-free technologies as they aspire to achieve development. The two significant benefits of the Green ITS strategy are first, to provide the environmental benefits of reducing greenhouse emissions and other environmental impacts and second, to enhance global green growth, which supports achievement of ecological sustainable development. Green ITS tools support achievement of the UN SDG 7, 13 and 15, which emphasize clean energy, climate action and ecological sustainable development, respectively. Future research directions include the formulation of a strategy to combat GHGs and design of a system to monitor carbon emissions and other waste remotely.
Keywords: 350; information and communication technology; green information technology; greenhouse gas emission; green information systems; carbon dioxide (CO2) emissions; people; planet and profit; legislation; ecology; green growth and sustainability